The First Seven Trumps of the Major Arcana (and the Fool) as Patterns for Pagan Leadership: Past, Present and Future - Muntean, Fritz (Pomegranate, 2002)
Covert leaders often insist on some version of the consensus method of decision making knowing (often intuitively) that consensus functions as a more or less subtle method of intimidation.